VLSI implementation of anti‐notch lattice structure for identification of exon regions in Eukaryotic genes. Issue 5 (21st May 2020) - Pathak, Vikas; Nanda, Satyasai Jagannath; Joshi, Amit Mahesh; Sahu, Sitanshu Sekhar
Abstract : In a Eukaryotic gene, identification of exon regions is crucial for protein formation. The periodic‐3 property of exon regions has been used for its identification. An anti‐notch infinite impulse response (IIR) filter is mostly employed to recognise this periodic‐3 property. The lattice structure realisation of anti‐notch IIR filter requires less hardware over direct from‐II structures. In this study, a hardware implementation of IIR anti‐notch filter lattice structure is carried out on Zynq‐series (Zybo board) field programmable gate array (FPGA). The performance of hardware design has been improved using techniques like retiming, pipelining and unfolding and finally assessed on various Eukaryotic genes. The hardware implementation reduces the time frame to analyse the DNA sequence of Eukaryotic genes for protein formation, which plays a significant role in detecting individual diseases from genetic reports. Here, the performance evaluation is carried out in MATLAB simulation environment and the results are found similar. Application‐specific integrated circuit (ASIC) implementation of the anti‐notch filter lattice structure is also carried out on CADENCE‐RTL compiler. It is observed that the FPGA implementation is 31 to 34 times faster and ASIC implementation is 58 to 64 times faster compared to the results generated by MATLAB platform with similar prediction accuracy.